The Influence of Family Environment and Learning Discipline on Students' Interest in Learning at State 4 Junior High School Tomohon - Lolong, Viany Marianus (International Journal of Information Technology and Education, 2024)
This study aims to examine the influence of the family environment and learning discipline on students' interest in learning at State 4 Junior High School Tomohon. Utilizing a quantitative research approach, this investigation involved a sample of 120 students selected through random sampling techniques. Data were collected through structured questionnaires designed to measure the variables of family environment, learning discipline, and students' interest in learning. The results revealed a significant positive correlation between the family environment and students' interest in learning, suggesting that supportive and nurturing family conditions contribute to higher levels of student engagement and enthusiasm for learning. Furthermore, learning discipline, characterized by consistent study habits, time management, and adherence to academic responsibilities, was found to be a critical factor in enhancing students' interest in their studies. Multiple regression analysis indicated that both the family environment and learning discipline collectively accounted for a substantial proportion of the variance in students' interest in learning, highlighting the combined impact of these factors. The findings underscore the importance of a conducive family environment and the establishment of disciplined learning habits as essential components in fostering students' academic motivation. The study concludes with recommendations for educators and parents to collaborate in creating supportive home environments and encouraging disciplined study practices to improve students' interest in learning. Future research directions include exploring the mediating effects of other psychosocial factors and extending the study to different educational settings to generalize the findings.